Microglial Cells: The Main HIV-1 Reservoir in the Brain - Wallet, Clementine; De Rovere, Marco; Van Assche, Jeanne; Daouad, Fadoua; De Wit, Stéphane; Gautier, Virginie; Mallon, Patrick W. G.; Marcello, Alessandro; Van Lint, Carine; Rohr, Olivier; Schwartz, Christian (Frontiers in Cellular and Infection Microbiology, 2019)
Despite efficient combination of the antiretroviral therapy (cART) which has significantly decreased mortality and morbidity of HIV-1 infection, a definitive HIV cure has not been achieved. Hidden HIV-1 in cellular and anatomic reservoirs is the major hurdle toward a functional cure. Microglial cells, the CNS resident macrophages, are one of the major cellular reservoirs of latent HIV-1. These cells are believed to be involved in both the emergence of drugs resistance and in reseeding peripheral tissues. Moreover, these long-life reservoirs are also involved in the development of HIV-1-associated neurocognitive diseases (HAND). Clearing these infected cells from the brain is therefore crucial to achieve a cure. However, many characteristics of microglial cells and of the central nervous system might preclude the eradication of these brain reservoirs. Better understandings of the specific molecular mechanisms of HIV-1 latency in microglial cells should help to design new molecules and new strategies preventing HAND and achieving an HIV cure. Moreover, new strategies are needed to circumvent the limitations associated to anatomical sanctuaries with barriers such as the blood brain barrier (BBB) that reduce the access of drugs.